Proteomic analysis reveals UV-B acclimation pathways in high-altitude Malbec berries and leaves - Murcia, Mauro Germán (2025)
High-altitude grapevine cultivation (Vitis vinifera L.) offers a sustainable strategy for producing premium wines under climate change. However, the molecular mechanisms of UV-B acclimation in field-grown grapes remain unclear. This study examined the effects of contrasting UV-B exposure (exclusion vs. full exposure) on Malbec grape leaves and berries at different developmental stages in a high-altitude vineyard in Mendoza, Argentina (1350 m a.s.l.). Quantitative proteomics revealed tissue- and stage-specific responses to UV-B, with leaves at veraison being the most responsive. Only two proteins—omega-hydroxypalmitate O-feruloyl transferase and chalcone isomerase—were consistently upregulated across all tissues and stages. In silico analysis of their promoters suggested regulation by light, hormones, and stress signals. UV-B altered both primary and secondary metabolism. Photosynthesis-related proteins were reduced in veraison leaves but increased in pre-veraison berry skins. Stress-related proteins showed opposite trends across development in berries. Polyphenol biosynthesis and antioxidant capacity were enhanced in +UV-B treatment, with transketolase, 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase (DHS), and chalcone isomerase emerging as key contributors to polyphenol accumulation. At veraison, UV-B induced lignin and flavonoid biosynthesis in leaves and promoted anthocyanin biosynthesis in berry skins, favoring the flavonoid 3′,5′-hydroxylase (F3′5′H) branch. UVR8 isoforms abundance correlated with anthocyanin-related responses, and a caffeoyl-CoA O-methyltransferase-2 isoform may mediate delphinidin methylation under UV-B stress. As berries matured, antioxidant defenses shifted from non-enzymatic to enzymatic mechanisms. This first proteomic study of high-altitude, field-grown grape berries provides new insights into UV-B acclimation and its potential to enhance grape and wine quality in a changing climate.